Getting Centered: A Meditation on Creating Pottery and Teaching Writing - Rosanne Carlo (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
Analogous thinking reminds a writing instructor of the historical influences that have shaped Rhetoric and Composition as a discipline that welcomes rather than excludes marginalized students.